On the performance of wireless sensor network time difference of arrival localization under realistic interference and timing estimation errors - Mohamed Adnan Landolsi; Hamood R Khan; Abdullah S Al-Ahmari; Ali H Muqaibel (International Journal of Distributed Sensor Networks)
The article addresses the modeling and performance analysis of wireless sensor network localization with direct-sequence spread-spectrum signals and network-based, time difference of arrival measurements. Realistic radio channel propagation and interference conditions are taken into account. Synchronization by means of a delay-locked loop is adopted for sensor signal tracking at the wireless sensor network anchor nodes. A comprehensive timing estimation analysis is presented with channel impairments, including pathloss attenuation, shadowing, multipath fading, and multi-access interference. The full statistics of the delay-locked loop tracking jitter are derived, which serves to assess the practically achievable synchronization accuracy and its variability with radio channel conditions and specific sensor location. The time difference of arrival measurements are then used for sensor localization based on an efficient iterative maximum likelihood estimation approach shown to outperform weighted least squares methods. Numerical results are presented to quantify the sensor localization accuracy limits, showing that the error is not uniform but varies considerably across the coverage region depending on the relative sensor position with respect to the different anchor nodes. Various factors related to changing wireless sensor network topologies and network loading conditions are also considered and their impact on localization performance is quantified.